Investigation of hepatitis A outbreak in a municipality in Northern Kerala - Nizar, Abdul; Haveri, Sheela P.; Binub, Kanniyan; Ishaque, Sherin; Sasi, Shilpa T.; Venugopal, Aishwarya K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Viral hepatitis A is a contagious viral disease affecting liver that can result in mild to severe illness. It can occur sporadically and in epidemics with a tendency of cyclical recurrence. India is considered to be hyper endemic region for HAV infection with very high infection rate in early years of life. Methods: An outbreak investigation was conducted in a municipality in Northern Kerala were a sudden rise in hepatitis A cases was reported by health authority to describe the outbreak in terms of person, place and time. Different sources were also inspected to identify probable cause for an outbreak in the area. Results: A total of 267 households were surveyed which included 84 households with at least one hepatitis A case and 183 household without cases. Individuals with hepatitis A counted up to 157. Mean age of the cases were 14.09±7.34 years. 89.1% took allopathic treatment and 7% took Ayurveda treatment. The total attack rate of the population was 0.29% and attack rate of ward 31 was 4.96%. Conclusions: Results of the outbreak investigation indicates that there is a need for establishment of an efficient water quality surveillance system and bringing about intervention for behavioural change in the population.